Re-envisioning Collaboration, Hierarchy, and Transparency in Audiology Education, Practice, and Research - Crukley, Jeff; Dundas, J. Andrew; McCreery, Ryan; Meston, Christine N.; Ng, Stella L. (Seminars in Hearing, 2012)
In this article five audiologists reflect individually and as a group on three perceived key challenges for their “cohort” of audiology clinicians, educators, and researchers. These three challenges were chosen based on practice, teaching and preceptoring, and research experiences and were inspired by related literature outside the young field of audiology. Audiology has the opportunity to look to older health professions that have faced similar challenges. The three challenges chosen for discussion were: collaboration, hierarchy, and transparency. A reflective dialogue ensued in which the group did not always come to an agreement. Yet the presentation of both our distinct and similar perspectives demonstrates the potentially generative and critical insights that can arise when we question the status quo and imagine what could be. This article is neither a research paper nor a literature review by any means. Rather, it serves as an invitation to ourselves and our colleagues to ask difficult questions about the way we are and to try to see ourselves through the eyes of others. In this way, as a new cohort, we may be able to continue to advance the field that has been built by audiology clinicians, educators, and researchers who came before us. And we strive to do this alongside the existing leaders who continue to work hard for audiology during challenging and changing times. Perhaps a critically reflective dialogue drawing from multiple perspectives can help us continue to improve, as a collective field, in a challenging economic climate.
Keywords: collaboration; critical reflection; dialogue; ethics; hierarchy; transparency